2022
DOI: 10.3389/fcimb.2022.969832
|View full text |Cite
|
Sign up to set email alerts
|

Changes of gut microbiota structure in rats infected with Toxoplasma gondii

Abstract: Toxoplasma gondii (T. gondii) infection can cause intestinal inflammation in rodents and significantly alters the structure of gut microbiota. However, the effects of different T. gondii genotypes on the gut microbiota of rats remain unclear. In this study, acute and chronic T. gondii infection in Fischer 344 rats was induced artificially by intraperitoneal injection of tachyzoites PYS (Chinese 1 ToxoDB#9) and PRU (Type II). Fecal 16S rRNA gene amplicon sequencing was employed to analyze the gut microbiota str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Moreover, PCoA revealed significant variation in the gut microbial communities of mice in both acute and chronic infection periods ( Figure 2B ). In line with previous studies, the structure and composition of the gut microbiota showed a dramatic variation after T. gondii infection ( 20 , 22 , 40 ). Previous studies have shown that during T. gondii infection, Firmicutes , Proteobacteria , and Bacteroidetes were the primarily affected phyla.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, PCoA revealed significant variation in the gut microbial communities of mice in both acute and chronic infection periods ( Figure 2B ). In line with previous studies, the structure and composition of the gut microbiota showed a dramatic variation after T. gondii infection ( 20 , 22 , 40 ). Previous studies have shown that during T. gondii infection, Firmicutes , Proteobacteria , and Bacteroidetes were the primarily affected phyla.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, some studies showed the diversity and composition of the gut microbiota in rodents infected with T. gondii by 16S amplicon sequencing ( 20 22 ). However, the functional features of the gut microbiota in mice with toxoplasmosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gut microbiota changes were determined with high-throughput sequencing technology. The differences of microbiota structure were caused by strains of different genotypes ( 40 ). The results showed that koumiss could increase the relative abundance of bacteria functioning in metabolism at 14 dpi, such as carbohydrate metabolism and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%